Milo : sticky notes and brain freeze - Silberberg, Alan. (New York : Aladdin, 2010)
In love with the girl he sneezed on the first day of school and best pals with Marshall, the "One Eyed Jack" of friends, seventh-grader Milo Cruikshank misses his mother whose death has changed everything at home.
School Library Journal starred, September 2010.
Kirkus Review, August 2010.
School Library Journal starred.
Kirkus Review.
6.3
3-6
Keywords: Grief -- Juvenile fiction; Death -- Juvenile fiction; Mothers -- Juvenile fiction; Friendship -- Juvenile fiction; Grief -- Fiction; Death -- Fiction; Mothers -- Fiction; Friendship -- Fiction; Grief -- Fiction; Death -- Fiction; Mothers -- Fiction; Friendship -- Fiction; Grief -- Fiction; Death -- Fiction; Mothers -- Fiction; Friendship -- Fiction